Підвищення якості розділового тонколистового штампування - Мірзак, В. Я.; Боков, М. В. (НТУ "ХПІ", 2014)
Експериментально доведено, що при штампуванні пластин ротора встановлення штампа на механічний компенсатор похибок системи «прес-штамп», порівняно із встановленням його без компенсатора, суттєво підвищує якість штампування, зокрема висота задирки зменшується за зовнішнім контуром на 93 % та за внутрішнім - на 45 %. Отриманий результат підтверджує доцільність використання механічних компенсаторів похибок системи «прес-штамп» з метою підвищення якості розділового тонколистового штампування.

It has been experimentally proven that while punching the rotor plates the mounting of the punch on the mechanic compensator considerably increases the quality of "press-punch" comparing with the mounting without the compensator. It occurs due to the decrease of the height of the agnail around the outer contour by 93 % and inner contour by 45 %. Distribution of the height of the agnail according to the perimeter of the plates' contour, which are punched and breached, a more even while mounting of the punch on mechanical compensator of faults of the system of "press-punch". This shows the decrease in the amplitude of the dynamic clearance. The result we have got proves the advisability of using mechanic compensators of faults of the system "press-punch" in order to increase the quality of separating thin plate punching.
Improvement of dividing thin-sheet stamping quality
Keywords: механічні компенсатори; тонколистове штампування; величина задирки; джерело похибок; пластини ротора; динамічне підстроювання; mechanic compensator; source of faults; rotor plates; dynamic adjusting; height of the agnail